Метрологические характеристики яркомера "Тензор-28" - Fodchuk, I. M.; Doktorovych, I. V.; Godovaniouk, V. M.; Butenko, V. K.; Yuriev, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The results of studies on the metrological characteristics of the “Tensor-28” luminance meter are presented. The device is designed to measure the average brightness of cathode-ray tube screens and other self-emitting surfaces.